Factor Affected Stunting Prevention in North Bengkulu District: a Qualitative Study - Yusran Hasymi; Yetti Purnama; Rostika Flora; Angesti Nugraheni; Nurlaili Nurlaili (Universitas Islam Bandung, 2022)
Stunting has been a considerable problem that indicates the poor level of public health in Indonesia. There are various efforts made to reduce stunting rates. The North Bengkulu regency has significantly successfully reduced the stunting rate over three years. This study aims to determine the measures to accelerate stunting reduction in the North Bengkulu regency. This is a qualitative descriptive study with data collected through focus group discussions and in-depth interviews. The study was implemented at the North Bengkulu regency in October 2021. There were five participants in the focus group discussion, and two participants were in-depth interviewed. The data were then transcribed verbatim and analyzed using the narrative analysis technique. The result of this study shows that the Head of the North Bengkulu Regency has been an outstanding leader with a strong commitment and vision to prevent stunting. The head of villages in North Bengkulu regency collaborates with public health centers in using village funds and determining the priority scale for stunting prevention. The involvement of cadres to empower the community is essential. The implementation of cross-program cooperation has been implemented. However, the cross-sectoral collaboration was not optimal. There is a difference in determining to stunt between cadres and nutrition workers. The training for stunting cadres and nutrition officers was carried out in stages. The cross-sectoral collaboration needs to increase to improve the program's effectiveness. The cadres and nutritionists need to train to determine stunting rates.